Mode-Matching Technique Along Oblique Surfaces and Applications to the Modeling of Curved Waveguides - Reis, Marcello Alves (2023)
Waveguides are widely used in telecommunications engineering for transmitting signals and manufacturing filters and other devices in the microwave applications. In this work, we present a formulation based on the mode-matching technique (MMT) for the analysis of discontinuities in cylindrical waveguides caused by curvatures in the longitudinal axis of the transmission line. We present and validate a technique for modal analysis of curved waveguides by approximating the curvature in a succession of oblique surfaces by means of their generalized scattering matrices (GSMs) extracted from the MMT. The present approach is a computationally efficient alternative for modeling curvature in cylindrical waveguides when compared to usual numerical brute force techniques (such as element-based, volume- based, or finite difference solutions). An algorithm is presented to compute the GSM matrix elements for different configurations of waveguide junctions. The novelty of the present method consists in considering the projection of electromagnetic fields onto oblique surfaces for the application of MMT. We present a series of numerical results that show that the technique presented in this study can guarantee results with good accuracy and precision when performing the analysis of the modal behavior of electromagnetic fields at discontinuities caused by curvatures.